Synthesis of a New Bicyclicgamma Lactam and Evaluation of their Anticancer Activity - Husam M. Kredy (Journal of Global Pharma Technology, 2018)
Highly diastereoselective synthesis of γ-lactams 5(a-b) based on the reaction of imines 3(a-b) with phenylsuccinic anhydride is described in this study in moderate yields. The synthesized compounds were tested in vitro for their antioxidant activity. The prepared compounds showed an antioxidant activity. Anticancer activity of the compounds 3(a-b) were tested against breast cancer cells (MCF7), which showed high efficiancy against MCF7 cell lines . The compounds were determined on the basis of the spectral studies using IR, 1H-NMR and13C-NMR.Keywords: γ-lactams, Antioxidant, Anticancer, MCF7.